Potential Use of Ultra High-Performance Fibre-Reinforced Concrete as a Repair Material for Fire-Damaged Concrete in Terms of Bond Strength - Baharuddin, Nur Khaida; Mohamed Nazri, Fadzli; Abu Bakar, Badorul Hisham; Beddu, Salmia; A. Tayeh, Bassam (International Journal of Integrated Engineering, 2020)
The strength of concrete structures deteriorates after exposure to fire. Strength loss varies with elevated temperature, fire duration, and the mechanical properties of concrete. Repairing and strengthening affected structures are important to improve their performances. Fire-damaged concrete has been repaired using fiber-reinforcing polymer. The superior properties of ultrahigh performance fiber-reinforced concrete (UHPFRC) make it suitable as a repair material. Furthermore, an excellent repair material should be able to bond properly with the substrate and maintain its structural integrity. The aim of this paper is to review the potential use of UHPFRRC as a repair material for fire-damaged concrete in terms of bond strength. Previous studies showed that developing efficient rehabilitation techniques that enable fire-damaged structures to be restored has some challenges. Whether UHPFRC can be used as a repair material particularly for fire-damaged concrete structure is recommended to be proven in future studies.